2014
DOI: 10.1002/biot.201400072
|View full text |Cite
|
Sign up to set email alerts
|

Isoforms of wild type proteins often appear as low molecular weight bands on SDS‐PAGE

Abstract: Immunoblotting, after polyacrylamide gel electrophoresis with sodium dodecyl sulfate (SDS-PAGE), is a technique commonly used to detect specific proteins. SDS-PAGE often results in the visualization of protein band(s) in addition to the one expected based on the theoretical molecular mass (TMM) of the protein of interest. To determine the likelihood of additional band(s) being nonspecific, we used liquid chromatography - mass spectrometry to identify proteins that were extracted from bands with the apparent mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(73 citation statements)
references
References 48 publications
7
66
0
Order By: Relevance
“…For example, five heat shock proteins (Hspa1a, Hspa8, Hspd1, Hsp90aa1, and Hsp90ab1) have their identified peptides evenly distributed across the entire protein with a high CR. In contrast, for more than 80% of these 40 genes, their proteins have one or more large regions lacking a detected peptide, also similar to what we have reported previously . It is worth mentioning that many lengthy proteins have repeated sequences, such as the Plec1 (Figure , lower panel), usually to reinforce some important functional domains.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…For example, five heat shock proteins (Hspa1a, Hspa8, Hspd1, Hsp90aa1, and Hsp90ab1) have their identified peptides evenly distributed across the entire protein with a high CR. In contrast, for more than 80% of these 40 genes, their proteins have one or more large regions lacking a detected peptide, also similar to what we have reported previously . It is worth mentioning that many lengthy proteins have repeated sequences, such as the Plec1 (Figure , lower panel), usually to reinforce some important functional domains.…”
Section: Discussionsupporting
confidence: 87%
“…Since it is unlikely that a large region of a protein sequence lacks a trypsin‐digested peptide for LC–MS/MS detection, as shown in Figures , and , a likely reason for the detection of the smaller group, generally speaking, is that the detected protein is either a degraded fraction or a smaller isoform lacking part(s) of the sequence. The LC–MS/MS results provide coverage rate (CR) of identified AAs (Table S2, column D), that is, the total AAs of all identified peptides as the percentage of the total AAs of the largest protein isoform listed in the NCBI database, as illustrated in Figure a using the 6PGL protein as an example . A larger CR indicates that the detected protein isoform is closer to the full‐length form, with a CR of 1 (100%), which will not occur in any real case, indicating that all AAs are LC–MS/MS identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, it was demonstrated that the CIK activity was significant inhibited by gentamicin, and further research revealed that a protein P43 was associated with CIK activity. To determine the identity of the P43 protein, 1-DE with LC-MS/MC was performed (24,25). The P43 protein was successfully identified as human haptoglobin.…”
Section: Discussionmentioning
confidence: 99%